Yesus Kristus Sang Ratu Adil Dalam Konsep Suku Jawa - Fajar Kristian Labeti, Yehuda; Fitriani , Kristiana (Sekolah Tinggi Teologi Injili Indonesia Palu, 2024)
Every human being wants to live a safe life, especially a safe life in Heaven. Many efforts and ways are made to get salvation. In the lives of Javanese people, the presence of Ratu Adil is highly anticipated, to provide a life of peace. This writing aims to look at the Javanese view of the Queen of Justice, where the concept is the same as what is written in the Bible, which was fulfilled in Jesus Christ. Jesus Christ is the Queen of Justice. This concept can be used in Christian mission, to reach more and more souls, to know, believe, and accept Jesus Christ as Savior, especially in the lives of Javanese people.